Potential and Challenges for Private Sector to Lead Warung Digitalization in Indonesia - Irlandi Paradizsa; Ety Rahayu (Universitas Islam Negeri Walisongo Semarang, 2022)
The purpose of this study is to understand the potential and challenges for the private sector to lead the process of warung digitalization to improve their business. MSMEs such as warung in Indonesia have been a tool for income generation for many people. Though the number of warungs that have leveled up is still minimum—most of their business are stagnant. This has resulted in their constant welfare situation. The approach used in this study is qualitative with the literature review method. This study finds that there is potential for the private sector to be the trailblazer in the digitalization process because of their characteristics and traits, the other actors’ situation, and the profit to be gained. Though, there are some challenges to be addressed, such as the lack of supporting infrastructure, minimal regulatory framework, and the need to train the warung owner.